Reaching beyond or beyond reach: challenges influencing access to higher education for care-experienced learners in Scotland - Peter Tormey (Scottish Journal of Residential Child Care)
Children in Scotland who spend time in the care of a local authority report lower educational attainment and are less likely to complete their secondary education than their non-care-experienced peers. Recent legislative changes designed to promote greater access to positive destinations for care-experienced people aims to enhance support into adulthood, promotes greater collaboration between public bodies, and increases non-repayable funding for care-experienced learners to study at college and university. This article will address the changes, unintended consequences and barriers that still persist from the period 2014 to the present. Education can be a catalyst for change and the rate of progress made to date to support care-experienced people into higher education must continue if Scotland is to achieve the ambition of a society where those with experience of care have the same equity of opportunities as the population at large.